Microbiome interplays in the gut-liver axis: implications for liver cancer pathogenesis and therapeutic insights - Xuran Wang; Bin Zhang; Runqiu Jiang (Frontiers in Cellular and Infection Microbiology, 2025)
Globally, primary liver cancer (PLC) ranks the most fatal malignancy. Most of the patients are in advanced stage of PLC at the very time they are diagnosed with it, accounting much for its poor prognosis. With the advancement of modern medical research and care system, the main etiology of PLC more and more switches from hepatitis viruses such as HAV, HBV, HCV, HEV to other causes like metabolism-associated steatohepatitis (MASH) and metabolic-associated fatty liver disease (MAFLD). As a result, it is of great necessity to find out new ways for treatment and early diagnosis to cope with this problem. Nowadays, as the mechanism of the Gut-Liver Axis in the formation of MAFLD, MASH and PLC has been gradually elucidated. The association between gut microbiome and the formation of PLC is of great significance to take an insight into. In this review, we present the concept of Gut-Liver Axis and its function in the mutual influence between gut microbiota and PLC from several aspects in which we will focus on the structure of gut barrier and the functional influences the gut microbiota have on the immune response and metabolic changes on human liver. Furthermore, we conclude the potential association of gut microbiota constitution with the PLC. Eventually, we hope this review can offer novel instructions for early diagnosis and treatment for liver cancer.